How Good is Your Memory Game Relates to Children's Expressive Language Development - Yulianingsih, Yuyun; Putri, Rengganis Kencana; Syamiyah, Syamiyah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This research was conducted based on the problems encountered in Group A RA Nurul Amal, Cileunyi District, Bandung Regency because not all children's Expressive Language development has developed well, such as there are children who cannot understand language, express language,and express ideas. This research aims to determine the relationship between the How Good is Your Memorygame activity and the development of expressive language in Group A RA Nurul AmalBandung District. This research uses a quantitative approach with correlational methods. The subjects in this research were group A RA Nurul Amal, Bandung District, consisting of 10 children. The data collection techniques used are observation, documentation,and performance. The results of data analysis show that the How Good is Your Memorygame obtained an average score of 75. This figure is in the interval 70 –79 in the good category. Meanwhile, the average score was 78. Expressive Language Development Thisfigure is in the interval 70 –79 in the good category. The relationship between the game How Good is Your Memoryand the development of expressive language has a correlation coefficient of 0.79. This correlation coefficient figure is in the interval 0.60 –0.799 in the strong or high category. The significant test results show thitung = 4.753 > ttabel = 1.860. This means that Ha (alternative hypothesis) is accepted and Ho (null hypothesis) is rejected. In other words, the game How Good is Your Memory has a positive relationship with Expressive Language Development in group A RA Nurul Amal Bandung District. The contribution of the game How Good is Your Memoryto the development of expressive language in early childhood is 62.41%. This means that there are still 37.59% other factors that influence the development of expressive language.